MULTICULTURAL EDUCATION IN MADRASAH DINIYAH AS PREVENTION OF RELIGIOUS CONSERVATISM - Ulil Hidayah; Benny Prasetiya (UIN Sumatera Utara Medan, 2019)
This article is written to give an overview of the conceptual view of Multicultural Education in Madrasah Diniyah (Islamic Primary School) as a Prevention of Religious Conservatism. This paradigm is based on issue anxiety which often assumes that Islamic education as an agent of change has not revealed its function to change moderate and tolerant religious perspectives. The model offered is planting the values of multicultural education in theMadrasah Diniyah. The existence of Madrasah Diniyah as a non-formal Islamic education institution, both those in the boarding school environment and those that stand independently, has played a large role in engendering to Muslim intellectuals through education and teaching that have given starting from the basic level to the upper levels of religious understanding.